A REVIEW OF THE LAW AND PROFESSIONAL PRACTICES ON THE ROLE OF NOTARIES IN REGULATION OF THE CAPITAL MARKET IN INDONESIA - Rizky Ratulinar; Heru Kuswanto (RADJA PUBLIKA, 2026)
This study examines the legal and professional practice of the role of notaries in regulating capital markets in Indonesia, focusing on the functions and responsibilities of notaries as public officials who play a role in ensuring legal certainty over documents and agreements that form the basis of capital market activities. In a regulatory context, the role of notaries is regulated by Law Number 2 of 2014 concerning the Office of Notaries, Law Number 8 of 1995 concerning Capital Markets, and various implementing regulations from the Financial Services Authority (OJK). Using a normative juridical approach, this study examines the involvement of notaries in the process of registering securities issuances, drafting deeds of establishment and amendments to issuers' articles of association, as well as ratifying underwriting agreements and information disclosure in the capital market. The results indicate that notaries play a strategic role in maintaining transparency, legality, and accountability in capital market activities, while also acting as a bridge between legal interests between issuers, investors, and regulators. However, field practice still presents challenges, such as a lack of understanding of capital market instruments among notaries and the potential for conflicts of interest in carrying out their duties. Therefore, it is necessary to improve the professional competence of notaries and align their professional code of ethics with the principles of good corporate governance to strengthen the integrity and effectiveness of legal oversight in the Indonesian capital market sector.